PEMUDARAN STRETCH MARK DENGAN OLIVE OIL DAN EKTRA LIDAH BUAYA(ALOE VERA) - Evi Hasnita; Silvia Silvia; Chantia Octazuria (Maternal Child Health Care, 2022)
Stretch Mark or Striae Gravidarum is a stroke occurs on the skin.  It may become dark in multigravida (Jannah, 2012). This study aimed to determine the differences stretch mark fading time by using Olive Oil and Aloe Vera Extract in postpartum in Tigo Baleh Community Health Center Bukittinggi in 2019.The type of this study was quasi experiment with non equivalent control group. It was conducted on April 2019. The populations were of all primigragravida postpartum mothers. Accidental sampling technique had been used to take the samples. The data were analyzed by statistics by using Independent T-test.The results of this study showed that the average fading time of stretch marks by using Olive Oil was 2.2000. Then, the average fading of stretch marks by using Aloe Vera Extract was 1.0000. Moreover, the statistical test obtained that there was a significance value of .001 <0.05. It indicates that there was a difference of stretch marks by using Olive Oil and Aloe Vera Extract. In short, Aloe Vera Extract was effective in fading stretch marks than Olive Oil in Postpartum mothers in Tigo Baleh Community Health Center Bukittinggi. Then, it is expected to choose Aloe Vera Extract in fading the stretch mark based on Standard Operating Procedure (SOP).  Keywords : Olive Oil, Aloe Vera Extract and Stretch Marks